ADOLESCÊNCIA(S) EM CONFLITO COM A LEI E A JUSTIÇA JUVENIL: (des)continuidades na aplicação das medidas socioeducativas - SOUSA, Mara Alves de (2017)
The present study addresses how the category "adolescence (s) in conflict with the law" has historically been demarcated in a "legitimate field of interventions" (and how this subsidizes the formation of opinion, decision making and intervention of the magistrate and professionals of the The judiciary). The analysis of the social history of adolescence (s) in conflict with the law demarcates this category as a social construction. It also discusses the role of the judiciary in the application of sentences for compliance with socio-educational measures and shows the challenges to ensure the full protection of adolescents in conflict with the law, and how this action in the field of juvenile justice can be The expression of symbolic power in the application of these measures. The challenges pointed out throughout this research were emphasized by the ECA and SINASE operator, in the legal universe, and by the psychosocial core. The considerations made throughout the study are based on the reports of those involved in this research and on the analysis of data from the reports cited in the course of the study. To uncover this problem was important to understand the specificity of intervention of the judiciary in the application of socio-educational measures and the reality of adolescents in compliance with these measures in São Luís / MA. The research is qualitative. The methodological proposal comprises the judiciary as a social field, correlated to social forces, demarcated in a field of struggles in defense of the rights (in constant dispute) of adolescents in conflict with the law. In order to support the proposed analysis, semi-structured interviews were carried out in order to construct the data. Therefore, the analyzed categories are problematized and interpreted from theorists who discuss this theme. The data highlight relevant aspects, to mention: the persistence of a distorted interpretation in the application and execution of socioeducational measures, a situation that reinforces the symbolic power in the field of juvenile justice; About a culture still rooted in the Minors Code (which persists in seeing the adolescent as the object of intervention and nullifies its condition as subject of rights); On the lack of structural conditions of the hospitalization units; On the fragile conditions for the execution of socio-educational measures in an open environment, considering the reality of the care institutions (regarding the fragile functioning of CREAS); And on the serious problem of social deprotection in which there is an expressive part of the adolescents in compliance with socio-educational measures in São Luís.